PERTIMBANGAN EKOLOGIS DALAM PENEMPATAN TINGGALAN MEGALITIK (Studi Kasus terhadap Sebaran Tinggalan Megalitik di Kawasan Jarai, Kabupaten Lahat, Sumatera Selatan) - sandy suseno (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2018)
This research explained about spread of megalithic site and its environment context at Jarai, Lahat Regency, South Sumatra. The objective of this research toexplore the reason of megalithic placing in Jarairegion. This research well focused at archaeological-spatial with macro-scale and the geographic informationsystem as analysis method.Based on this research, it is found of spread of megalithic sites be related to naturalresources around that.